One Health Aotearoa: a transdisciplinary initiative to improve human, animal and environmental health in New Zealand - Harrison, Sarah; Baker, Michael; Benschop, Jackie; Death, Russell; French, Nigel; Harmsworth, Garth; Lake, Robin; Lamont, Iain; Priest, Patricia; Ussher, James; Murdoch, David (New Zealand Science Review, 2020)
The following article, Harrison, S., Baker, M.G., Benschop, J. et al. One Health Outlook 2, 4 (2020), was published online by BMC on 31 January 2020 at: https://doi.org/10.1186/s42522-020-0011-0. It is © The Author(s) 2020, but is Open Access and is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided that appropriate credit is given to the original author(s) and the source, a link is provided to the Creative Commons license, and any changes are indicated. Permission to republish the paper here has been obtained from the authors, and no changes have been made to the text.